2019
DOI: 10.3349/ymj.2019.60.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis after Cataract Surgery in Korea: A Nationwide Study Evaluating Incidence and Risk Factors in a Korean Population

Abstract: Purpose To assess the nationwide rate of acute postoperative endophthalmitis (APE) after cataract extraction in Korea and to evaluate potential risk factors thereof. Materials and Methods Nationwide insurance claims data from July 2014 to June 2017 were reviewed. All patients with phacoemulsification or extracapsular/intracapsular cataract extraction were included. Exclusion criteria were combined glaucoma surgery or total vitrectomy or when the patient had a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(51 reference statements)
0
20
3
2
Order By: Relevance
“…The DM is a component of metabolic syndrome, and the presence of DM correlates with the development of postoperative complications in cataract surgery [ 15 , 18 , 26 ]. In a previous study, DM was associated with a higher rate of cystoid macular edema [ 8 ], and other studies demonstrated that DM patients were prone to develop postoperative endophthalmitis [ 10 , 27 ]. In the current study, DM is also a significant risk factor for major postoperative complications of cataract surgery with a prominent aOR of 2.818, consistent with the results from previous research.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The DM is a component of metabolic syndrome, and the presence of DM correlates with the development of postoperative complications in cataract surgery [ 15 , 18 , 26 ]. In a previous study, DM was associated with a higher rate of cystoid macular edema [ 8 ], and other studies demonstrated that DM patients were prone to develop postoperative endophthalmitis [ 10 , 27 ]. In the current study, DM is also a significant risk factor for major postoperative complications of cataract surgery with a prominent aOR of 2.818, consistent with the results from previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Except for DM, other metabolic diseases, including hypertension and dyslipidemia, and hyperlipidemia, also correlated with the development of postoperative complications in the current study. Hypertension may lead to poor postoperative status, including delay wound healing in root canal treatment and a higher rate of postoperative endophthalmitis [ 10 , 33 ]. Conversely, the dyslipidemia status can damage the vascular endothelium and lead to the formation of atherosclerotic plaque [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations